STRATEGI PENGEMBANGAN BADAN USAHA MILIK DESA GUNUNG MULIA DENGAN PENDEKATAN ANALISIS SWOT DI DESA GRENDEN KECAMATAN PUGER - Ega Afri Wulandari; Maheni Ika Sari; Achmad Hasan Hafidzi (Growth, 2021)
This study aims to formulate a development strategy for the Badan Usaha Milik Desa (BUMDes) of Gunung Mulia Grenden, Puger and determine the priority development strategies that can be implemented by BUMDes. Analysis of the data used is a SWOT matrix (Strength, Weakness, Opportunity, Threath). This study uses a descriptive type of research with a qualitative approach, which is a research method used to examine the condition of natural objects. The results showed that the IFAS matrix analysis had a total score of 3,312. The total value of the EFAS matrix is ​​3,273. On the IE Matrix (Internal Eksternal) BUMDes Gunung Mulia Grenden, Puger is in quadrant I, which means that it is in a position to grow and be built. From the results of the research on alternative organizational strategies that have been obtained and practical researchers to determine the development of strategies for the Gunung Mulia BUMDes that are in accordance with the situation and conditions as well as the objectives of the Gunung Mulia BUMDes. The priority of the development strategy is to develop business units based on the potential of Grenden Village, increase BUMDes promotion and business activities online through social media (WA, FB, IG, Youtube) and marketplace, increase BUMDes capital through the development of cooperation with third parties or companies (CSR). ), socializing the BUMDes program by the management to increase public knowledge about BUMDes so that it has an impact on community participation in BU management and innovating and modifying businesses that can be done in times such as the establishment of agro-tourism villages.